2009
DOI: 10.1007/s10853-009-3334-x
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence properties of pyrolytic boron nitride

Abstract: Abstract.We report on spectroscopic study of pyrolytic hBN (pBN) by means of time-and energyresolved photoluminescence methods. A high purity of pBN samples (though low crystallinity) allows complementary information about excited states involved into the luminescence process. We affirm our recent conclusions about the impurity-related nature of most of the fluorescence bands in microcrystalline hBN. In addition, a broad band centred at 3.7 eV previously not considered because of its superposition with an inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
20
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 36 publications
4
20
1
Order By: Relevance
“…32,35 According to the previous studies, the increase of planar faults in hBN can reduce the DUV luminescence efficiency and give rise to a decreased DUV to $300 nm emission ratio. 32,36 However, our results in Figure 3 are on the contrary that the DUV to $300 nm emission ratio increased with ball milling time. So the relative decrease of the $300 nm band is contributed by another factor, which is discussed below.…”
contrasting
confidence: 72%
“…32,35 According to the previous studies, the increase of planar faults in hBN can reduce the DUV luminescence efficiency and give rise to a decreased DUV to $300 nm emission ratio. 32,36 However, our results in Figure 3 are on the contrary that the DUV to $300 nm emission ratio increased with ball milling time. So the relative decrease of the $300 nm band is contributed by another factor, which is discussed below.…”
contrasting
confidence: 72%
“…[ 7,9–15 ] Museur et al reported three photoluminescence (PL) bands at the energies of 5.3, 3.75, and 3.1 eV for pyrolytic hBN (pBN) samples. [ 9 ] pBN samples are high‐purity samples, free of carbon and oxygen. The emission bands at around 5.3 and 3.57 eV were found to be donor−acceptor pair (DAP)‐type transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several photo-and cathodoluminescence studies [3][4][5]7,8,[32][33][34] have been published in an effort to understand the electronic and optical properties of h-BN. According to these reports, exciton formation, impurities and defects are responsible for h-BN luminescence, due to the formation of acceptor and donor levels in the bandgap.…”
Section: Introductionmentioning
confidence: 99%